FILSAFAT CINTA MUHAMMAD IQBAL - Suprapto, Rohmat (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2014)
Abstract: In the academic world, Iqbal is known as a poet, philosopher, sufism, historian, and politician. The professions which he elaborated could reach the peak levels in their respective fields of life. In addition to his character, the concept he introduced and the reflection of his life were not only a synergy with Islamic law that derived from the Qur'an and As Sunnah, but also indeed both codices that leads his way of life. Due to these facts, he was dubbed as greatest Mujaddid in 20-th century.One of the concepts that makes him well recognized is the concept of love as expressed in a series of poems and was described as' ishq. 'Ishq is given from birth as God's grace by which will be cultivated and tested during the life to encounter all forms of humanity impairment leading to the perfection of life with the title 'the perfect Manâ€™. Inside there is a blend of love and sense of intellect, love and reason, vision and power that are manifested in acts of prayer and work of scientists, and crystallized in the life of mysticism and scientism. Abstrak:Dalam dunia akademik, Iqbal dikenal sebagai penyair, filosof, sufisme, sejarawan, dan politikus. Profesionalisme yang ia tekuni mencapai tingkat puncaknya di atas masing-masing bidang kehidupan ini, di samping karakternya, baik level konseptual maupun refleksi hidupnya, bukan hanya sinergi dengan syariat Islam yang bersumber kepada Al-Quran dan sunnah Rasululillah, melainkan memang kedua naskah kuno itulah yang menuntun jalan hidupnya.Pantas kalau ia digelari mujaddidterbesar di abad 20.Satu diantara konsep yang menjadikan ia memperoleh nama besar adalah konsepnya tentang cinta yang diungkap dalam rangkaian puisi dan ia sebutnya sebagai â€˜isyq. â€˜Isyq diperoleh sebagai bawaan lahir dari rahmat Tuhan yang dengannya dipupuk dan diuji dalam medan kehidupan sambil menepis segala bentuk pelemahkan kemanusian menuju ke-sempurna-an hidup dengan predikat â€˜the perfect Manâ€™. Di dalamnya berpadu antara cinta dan akal intelek, love and reson, vision and power yang diwujudkan dalam tindak shalat dan kerja ilmuwan, dan mengkrital dalam kehidupan mistisime syarâ€™i Keywords: cinta, intelek, the Perfect Man, khalÄ«fah AllÄh, waá¸¥dah al-wujÅ«d.